Mekanisme transmisi konsekuensi ekonomi dari perubahan kebijakan akuntansi: studi literatur - Az-Zahra, Luthfia Cahya (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the influence of political intervention in the standard-setting process, considering the perspectives of economic consequences theory and positive accounting theory. Using a literature review method, this study analyzes various empirical studies previously conducted on this topic. The results show that political intervention in standard setting is a complex and multidimensional phenomenon. Economic consequences theory explains that political decisions in accounting can have significant economic impacts, both on individual companies and on the overall economy. Meanwhile, positive accounting theory provides a framework for understanding why certain parties have incentives to influence the standard-setting process. This study highlights the importance of balancing political, economic, and technical considerations in the standard-setting process. In addition, this study also identifies several challenges and implications of political intervention in standard setting.